Doodem and council fire: anishinaabe governance through alliance - Bohaker, Heidi (The Osgoode Society for Canadian Legal History, 2020)
"Combining socio-legal and ethnohistorical studies, this book presents the history of doodem, or clan identification markings, left by Anishinaabe on treaties and other legal documents from the seventeenth through the nineteenth centuries. These doodems reflected fundamental principles behind Anishinaabe governance that were often ignored by Europeans, who referred to Indigenous polities in terms of tribe, nation, band, or village - classifications that failed to fully encompass longstanding cultural traditions of political authority within Anishinaabe society. Making creative use of natural history, treaty pictographs, and the Ojibwe language as an analytical tool, Doodem and Council Fire delivers groundbreaking insights into Anishinaabe law. The author asks not only what these doodem markings indicate, but what they may also reveal through their exclusions. The book also outlines the continuities, changes, and innovations in Anishinaabe governance through the concept of council fires and the alliances between them. Original and path-breaking, Doodem and Council Fire offers a fresh approach to Indigenous history, presenting a new interpretation grounded in a deep understanding of the nuances and distinctiveness of Anishinaabe culture and Indigenous traditions."-- Provided by publisher.